Exploring Cultural Relevance in Entrepreneurship: The Case of Indigenous Igbo Business Mentoring (Igba-boyi) - Dare Ojo OMONIJO1; Chiamaka Ogechukwu JOE-AKUNNE2; Michael C. ANYAEGBUNAM2; Edith AWOGU-MADUAGWU3; Olusola B. OKUNLOLA4 (Communications of International Proceedings, 2020)
Entrepreneurial activities could be perceived as an act of establishing businesses, indulging in risks that involve finance in profits anticipation. Of all tribes in Nigeria, it appears no one has done better than the Igbos in establishing small-scale businesses through a special scheme known as “Nwa-boyi” that evolved from their cultural background. In spite of the prevalence of the scheme in Igbo land, southeast Nigeria and its application for exploits in small scale businesses by the Igbos in villages, town and cities across Nigeria, the connectivity of “Nwa-boyi” with the culture of Igbo land is seemed not to have been fully illustrated in academic literature. The present article intends to address this gap in knowledge using data from secondary source and content analysis as the methodology. The article strives to discover how the value, beliefs and other cultural factors of Ndigbos have contributed positively to the success of indigenous Igbo business mentoring. The paper commends the scheme but suggests its inclusion in the customary law of Igbo land to safeguard against fraud or a breach of agreement between the ‘Oga’ and ‘Nwa-boyi’
Keywords: Cultural Relevance; entrepreneurship; indigenous Igbo business mentoring